2014
DOI: 10.4193/rhin13.055
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation of an olfactory test: the odour in bottle test. [corrected].

Abstract: Aim:Our objective was to create a culturally appropriate test of olfactory perception based on the Sniffin' Sticks test to determine the effects of age, gender, education level, and smoking on patients' sense of smell in Diyarbakır, Turkey. Material and Methods:A total of 180 subjects participated in the study including 111 males. These were patients at the Dicle University Otolaryngology Polyclinic and voluntarily participated in the study between June and December 2012. They were subdivided according to age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Three main subtests are evaluated when olfactory function is screened—odor identification, olfactory threshold, and odor discrimination. It has long been demonstrated that females outperform males in odor identification 16–20 . However on meta‐analysis comparing gender‐related differences in odor identification, this difference was only seen in patients aged 18 to 50 years 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main subtests are evaluated when olfactory function is screened—odor identification, olfactory threshold, and odor discrimination. It has long been demonstrated that females outperform males in odor identification 16–20 . However on meta‐analysis comparing gender‐related differences in odor identification, this difference was only seen in patients aged 18 to 50 years 16 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that these changes are secondary to contributions from fluctuating gonadal steroid levels and anatomical differences of the olfactory system not yet fully elucidated 16 . No significant differences have been noted based on sex for odor discrimination or olfactory threshold 19 …”
Section: Resultsmentioning
confidence: 99%